Perfil gênico no oviduto bovino de fêmeas Nelore e Aberdeen angus - Fontes, Patricia Kubo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The oviduct has an important role in mammal reproduction, promoting a favorable microenvironment for oocyte maturation, sperm storage and capacitation, fertilization, transport of gametes and early embryo development. Anatomically and functionally, the oviduct is divided in three regions: infundibulum, ampulla and isthmus. The oocyte and the sperm enter in opposite sides of the oviduct, respectively infundibulum and isthmus, and are transported to the fertilization site, the ampulla. Reproductive success is directly related to appropriate timing of gamete transport to the fertilization site, as well as a precise time of embryo transport to the uterus, to obtain the capacity of implantation. The coordination and regulation of oviductal functions are complex and under endocrine, paracrine and autocrine effects, which temporally and spatially alter the transcription and translation of several factors. Therefore, this study aimed to evaluate the effect of reproductive biotechnologies, specifically ovarian superstimulation, as well as genetic and physiological reproductive characteristics in the transcriptional profile of several factors in the bovine oviduct. To do so, we evaluated the effects of inducing multiple ovulation in Nelore cows (data presented in the first manuscript), and the effects of the influence of genetic selection of animals with high follicle count in Nellore and Aberdeen Angus heifers, in the initial period post-ovulation (data presented in the second manuscript), in gene expression related to gametes transport and fertilization. The results demonstrated that ovarian superstimulation modulates the expression of some genes related to oviductal contractility in Nelore cows and ovulation is the main factor responsible for transcriptional control in bovine oviduct, with less or no impact of breed and ovarian follicle count

O oviduto possui papel essencial na reprodução de mamíferos, promovendo um microambiente favorável para a maturação oocitária, estocagem e capacitação do espermatozoide, fertilização, transporte dos gametas e desenvolvimento inicial do embrião. Anatomicamente e funcionalmente, o oviduto é dividido em três regiões principais: infundíbulo, ampola e istmo. O oócito e o espermatozoide entram nos lados opostos do oviduto, respectivamente no infundíbulo e istmo, e são transportados até a ampola, local onde ocorre a fertilização. O sucesso reprodutivo está diretamente ligado a temporização apropriada do transporte dos gametas ao local da fertilização, bem como, a precisão no tempo de transporte do embrião até o útero, para a aquisição da capacidade de implantação. A coordenação e regulação das funções do oviduto são complexas e estão sob efeitos endócrinos, parácrinos e autócrinos, os quais alteram temporalmente e espacialmente a transcrição e tradução de diversos fatores. Diante disso, o presente trabalho visou avaliar o efeito de biotecnologias reprodutivas, especificamente da superestimulação ovariana, bem como de características genéticas e fisiológicas reprodutivas no perfil transcricional de diversos fatores no oviduto bovino. Para tanto, foram avaliados os efeitos da indução de múltiplas ovulações em vacas da raça Nelore (dados apresentados no primeiro manuscrito), bem como os efeitos da influência da seleção genética de animais com alta contagem folicular em novilhas da raça Nelore e Aberdeen Angus, no período inicial pós ovulação (dados apresentados no segundo manuscrito), na expressão de genes relacionados ao transporte de gametas e fertilização. Os resultados demonstram que a superestimulação ovariana modula a expressão de alguns genes relacionados à contratilidade do oviduto em vacas da raça Nelore e que a ovulação é principal fator responsável por controlar ...
Keywords: Nelore (Zebu); Aberdeen-angus (Bovino); Falópio, Trompas de; Reprodução animal; Expressão gênica; Biotecnologia animal; Fallopian tubes